KEJAHATAN PORNOGRAFI TERHADAP ANAK DI DUNIA MAYA - Thresia Hilda Mathelda Yenkase Krey; Winna Amelia Alfrida Senandi (JURNAL PENGABDIAN PAPUA, 2023)
This science and technology implementation activity was carried out through counseling entitled "The Crimes of Pornography to Children in the Virtual World". This activity was carried out at the Abara Church of Kampung Enggros and the Alpha Omega Hamadi Pentecostal Church with participants from school age children to teenagers and young people. The purpose of this service is to provide an understanding of various kinds of child pornography crimes in cyberspace, provide information about the steps to prevent the occurrence of pornographic crimes in cyberspace, and provide an understanding of legal sanctions for pornography crimes against children in cyberspace. It was seen in this activity that the counseling participants were enthusiastic in receiving the material provided, indicated by various responses and good responses from the participants who asked questions during the counseling. This activity is expected to be carried out regularly, not only for teenagers and young people, but also for parents as a form of prevention effort to reduce the number of victims of child pornography crimes in cyberspace in the future.Keywords: Pornography; Children; Law